2019
DOI: 10.1021/jacs.9b11988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dielectric Environment upon Isotope Effects on Glycoside Heterolysis: Computational Evaluation and Atomic Hessian Analysis

Abstract: Isotope effects depend upon the polarity of the bulk medium in which a chemical process occurs. Implicit solvent calculations with molecule-shaped cavities show that the equilibrium isotope effect (EIE) for heterolysis of the glycosidic bonds in 5′methylthioadenosine and in 2-(p-nitrophenoxy)tetrahydropyran, both in water, are very sensitive in the range 2 ≤ ε ≤ 10 to the relative permittivity of the continuum surrounding the oxacarbenium ion. However, different implementations of nominally the same PCM method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…There was a near-perfect linear correlation between the EIE values resulting from the full and atomic Hessians over the range of relative permittivity 2 r e r 80: all the variation was captured by the influence of the dielectric upon the isotopically substituted atom alone. 12 The QM/MM rigid potential-energy scans along the three H a normal modes of the CH, THP, CP and THF cations indicate that the harmonic approximation is very good for small displacements from equilibrium, just as it was previously shown to be for the symmetric CH stretch mode of the methyl cation. 11…”
Section: Qm/mm Harmonic Eiesmentioning
confidence: 62%
See 1 more Smart Citation
“…There was a near-perfect linear correlation between the EIE values resulting from the full and atomic Hessians over the range of relative permittivity 2 r e r 80: all the variation was captured by the influence of the dielectric upon the isotopically substituted atom alone. 12 The QM/MM rigid potential-energy scans along the three H a normal modes of the CH, THP, CP and THF cations indicate that the harmonic approximation is very good for small displacements from equilibrium, just as it was previously shown to be for the symmetric CH stretch mode of the methyl cation. 11…”
Section: Qm/mm Harmonic Eiesmentioning
confidence: 62%
“…Very recently we calculated the harmonic EIE K H /K D for transfer of two oxacarbenium cations (tetrahydrofuranyl, THF and tetrahydropyranyl, THP) and their carbocyclic congeners (cyclopentyl, CP and cyclohexyl, CH) from water to cyclohexane by means of QM/MM modelling with explicit solvent. 12 Atomic Hessian analysis, whereby the full Hessian was reduced to the elements belonging to a single atom at the site of isotopic substitution, revealed a remarkable result: the influence of the solvent environment on the EIEs was essentially captured completely by only a 3 Â 3 block of the Hessian, although these values needed to reflect correctly the influence of the whole environment.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of a Hessian calculated only for few atoms out of a larger system being isotopically substituted for the correct prediction of isotope effects has been addressed in a very recent study on the effect of dielectric environments on isotope effects. 31 Świderek et al in their work have demonstrated that a small set of atoms (a moiety isotopically substituted) instead of the entire system can be used for isotope effect prediction because as long as the influence of the whole environment on this small set is reflected from the IEs obtained from these two approaches are basically the same. This is in contrast to our observation of improved prediction when only a subset of total number of normal modes of a system is used for isotope effect prediction.…”
Section: Discussionmentioning
confidence: 99%
“…It is often assumed that trends in KIEs may be related to structural changes in TSs understood in terms of geometries and bond orders, 10 , 22 but recent computational studies have suggested that changes in the electrostatic environment of a TS 20 , 21 , 23 , 24 or its stabilization by C α H···O hydrogen-bonding interactions might also be significant. 21 , 25 As part of a program of investigation into factors underlying 2° KIEs and their meaningful interpretation, the possible contribution of anharmonicity has also been considered, but this has not been found to be significant for equilibrium isotope effects (EIEs).…”
Section: Introductionmentioning
confidence: 99%
“…However, the values of the force constants in this symmetrical 3 × 3 matrix must accurately reflect the influence of the whole supramolecular environment. 24 …”
Section: Introductionmentioning
confidence: 99%